Construction of a multicolored emission tetraphenylethene derivative in response to multiple stimuli. (November 2021) - Xie, Weiwei; Chang, Xiaoyong; Chen, Liangliang; Liu, Lianmei; Huang, Guangxi; Li, Bing Shi
Abstract: Novel multiple stimuli-responsive fluorescent materials have diverse functions and are in high demand in practical applications. In this work, we reported a simple but versatile tetraphenylethene (TPE) derivative 1, whose appearance and fluorescence color were sensitive to mechanical, thermal, solvent vapor and UV light stimuli. It displayed tricolored mechanochromic and photochromic behavior with high contrast (variation of emissive wavelength is more than 100 nm). Moreover, the relationship between intermolecular interactions and fluorescence property was clarified through the investigation of its polymorphs. The multiple stimuli-responsiveness of compound 1 is ideal for preparing advanced anti-counterfeiting material. Graphical abstract: Multiple stimuli-responsiveness and anti-counterfeiting application of a novel tetraphenylethene derivative was demonstrated. Image 1 Highlights: Tricolored mechanochromic property. Photochromic behavior with high contrast. Advanced anti-counterfeiting material.